Desnutrición y su relación con el factor socio-económico en los niños del Barrio Zhucos - Ortiz Chamba, Robert Vinicio (2016)
In malnutrition, recognize different risk factors and its high prevalence, is intimately linked to the socio-economic level (Palli & Mejía, 2012). This descriptive study, aimed to determine the frequency ofmalnutrition in relation to socio-economic factors in a group of 27 15 children under age 5 in the Zhucos district, which was used for the implementation of who growth standards; and GRAFFAR scale, applied them to the parents of children who presented malnutrition. We found that 50% of girls and 27% of children presented malnutrition. The socio-economic factor of the majority of the families of children with malnutrition was to 100% have incomplete basic education levels, do not have a fixed job, have mixed construction (adobe and concrete) homes; they do not have drinking water or sewerage, there is improper classification and disposal of waste; 75% live in overcrowded; 29% made the disposition of their excreta to open country and 71% in cesspool , 64% of the families living in conditions of tenants, by what are considered as risk factors for health. What if there is a close relationship between malnutrition and the socio-economic factor. KEY WORDS: Malnutrition, socioeconomic level, scale GRAFFAR.